Phenology and yield response of wheat varieties as influenced by sowing dates at gonde and ardayita seed production farm, Ethiopia - Tatek Tamiru; Girma Gemedi; Berhanu Debelu; Henok Tesfaye (Research in Agriculture Livestock and Fisheries, 2023)
Wheat is one of Ethiopia's main foods, contributing to daily caloric consumption. Due to environmental conditions such as distribution and length of the rainy season shifting from time to time elsewhere, particularly at Gode and Ardayita seed production farm, sowing timing and varietal selection are key factors for low yield of wheat crop. This Experiment was designed in a randomized complete block design with three-replications which contain four sowing dates, ranging from June 17 to July 18 at ten-day intervals, and four wheat varieties namely Kingbird, Hidase, Picaflor, and Ogolcho combined to form 16 treatments. According to the result, on days to heading, there was a significant interaction effect of variety and location and the highest number of days (70.42) was obtained at the Ardayita location on Kingbird variety. On the day of heading, there is also a substantial interaction effect of location and sowing date, the maximum days (72.00) were observed at Ardayita on the early sowing date (June-17). The maturity dates of the two locations varied significantly, the longer (116.17) days were recorded at Ardayita. The effect of variations on days to maturity of varieties also significant, Ogolcho variety had the highest maturity (120.04) days. Date of sowing also has a significant effect on maturity date; the highest number of days (116.96) was recorded on June 17 sowing date. The grain filling period significantly vary among the varieties, the Ogolcho variety had the highest number of days (53.25). Grain filling period also had significant variation on date of sowing; the earliest sowing date (June 17) has the longest date (49.96). On the other hand, location had no effect on the grain-filling period, plant height and seed yield. Sowing date and location significantly interact on grain yield of wheat. The maximum (6.38 ton ha-1) seed yield was recorded at Gonde location on second (June 28) sowing date and Ardayita place obtained highest yield at first sowing date (June 17). There was a significant interaction between sowing date and varieties on yield of wheat. From the result Hidasse variety obtained highest yield (6.58 ton ha-1) on the second sowing date (June 28) whereas the Ogolch variety recorded highest (6.28 ton ha-1) at the first sowing date (June 17). Res. Agric. Livest. Fish. Vol. 10, No. 2, August 2023: 133-145